2019
DOI: 10.1002/jcla.23019
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the long noncoding RNA RP11‐169D4.1‐001 in Hypopharyngeal Squamous cell carcinoma tissue and its clinical significance

Abstract: Background: Increased research efforts have demonstrated that lncRNAs are associated with multiple head and neck tumors and play important roles in cancer. We previously found that RP11-169D4.1-001 plays a tumor-suppressive role in laryngeal cancer, but its function in human hypopharyngeal squamous cell carcinoma (HSCC) remains unknown. Thus, this research aimed to analyze the relationship between RP11-169D4.1-001 expression and HSCC clinicopathological features. Methods: Real-time quantitative reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…11,12 Accumulating evidence indicates that aberrant expression of lncRNAs may be associated with various cancers including OS, and serve as prognostic, diagnostic, and therapeutic biomarkers in OS. [13][14][15][16][17][18][19][20]…”
mentioning
confidence: 99%
“…11,12 Accumulating evidence indicates that aberrant expression of lncRNAs may be associated with various cancers including OS, and serve as prognostic, diagnostic, and therapeutic biomarkers in OS. [13][14][15][16][17][18][19][20]…”
mentioning
confidence: 99%
“…In the past, the ncRNA expression spectrum of LSCC mainly focused on miRNA and lncRNA, our previous research revealed that miR‐34a, 10 AC026166.2‐001 11 and RP11‐169D4.1‐001 12 were closely related to the occurrence of LSCC. A recent study found that lncRNA MALAT1 was overexpressed in LSCC tissues and highly correlated with the 5‐year survival of patients; it triggers the resistance of LSCC to chemotherapy drugs by promoting metastasis and inhibiting tumor cell apoptosis 13 .…”
Section: Discussionmentioning
confidence: 99%
“…For advanced primary tumor(s) or previously treated dysfunctional larynx, total or partial laryngectomy plays a critical role and remains the primary method of treatment 5 . These surgical methods influence the capacity of phonation and airway protection during swallowing 6 . The need for laryngectomy persists among individuals with a dysfunctional larynx and poor quality of life.…”
Section: Introductionmentioning
confidence: 99%